PEMBAGIAN HARTA BERSAMA DALAM PERKAWINAN POLIGAMI - Sofwan Ahadi (Faculty of Sharia and Law UNISNU Jepara, 2014)
Al-Qur'an and the hadis do not regulate in detail the division of joint property in a polygamous marriage. That is why, KHI (the Compilation of Islamic Law) set the regulation on the basis of accepted practices in public life in Indonesia and not contrary to the principles of the shari'ah. In the Islamic legal system, this kind of habit called